Risks affecting the performance of Ethiopian domestic road construction contractors. Issue 4 (12th March 2023) - Wubet, Worku Asratie; Burrow, Michael; Ghataora, Gurmel
Abstract: The government of Ethiopia (GOE) has been working to enhance the capacity of Ethiopian domestic contractors (EDCs) over the past three decades. This has enabled the development of several private and public construction firms. However, the performance of EDCs is still a matter of concern. The aim of this paper is, therefore, to identify and prioritize risks of EDCs operating in the federal road construction projects. Forty-seven risk events were identified through an in-depth literature review. A questionnaire survey was conducted with professionals from the three main contracting parties (contractors, consultants, and the client) to prioritize the identified risk events in terms of their relative significance. The study outlined the ten most significant risk events namely, shortage of cash, inadequate planning, lack of access to foreign currency, delay in possession of site, frequent breakdown of equipment, delay in delivery of material and equipment, financial failure, inflation, delay in payments and poor commitment and coordination within the contractors' team. This study provides an insight into contractors' risks with a focus on domestic contractors engaged in the road sector. The findings of this study will be helpful to construction firms to develop an appropriate risk management system to effectively mitigate their risks.